2016
DOI: 10.1007/s11060-016-2158-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the PI3K inhibitor buparlisib (NVP-BKM120) suppresses the growth of established patient-derived GBM xenografts and prolongs survival in nude rats

Abstract: Glioblastomas (GBMs) are aggressive brain tumours with a dismal prognosis, despite combined surgery, radio- and chemotherapy. Close to 90 % of all GBMs harbour a deregulated PI3K pathway, which is essential in regulating central cellular functions such as proliferation, cell growth, motility and survival. Thus, PI3K represents a potential target for molecular therapy in GBM. We investigated the anti-tumour efficacy of the PI3K inhibitor buparlisib (NVP-BKM120) in GBM cell lines in vitro and in vivo, when treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Buparlisib (BKM120) has been proposed as a potential targeted therapy for GBM [ 30 33 ]. It is currently being investigated in a Phase II clinical trial in GBM patients (ClinicalTrials.gov, NCT01339052).…”
Section: Introductionmentioning
confidence: 99%
“…Buparlisib (BKM120) has been proposed as a potential targeted therapy for GBM [ 30 33 ]. It is currently being investigated in a Phase II clinical trial in GBM patients (ClinicalTrials.gov, NCT01339052).…”
Section: Introductionmentioning
confidence: 99%
“…Since the blood-brain-barrier limits availability of drugs to the central nervous system (CNS), brain tumors are generally not considered attractive malignancies for initial drug screenings. However, BKM120 penetrates the blood-brain-barrier, and clinical evaluations in glioblastoma are being conducted [ 22 , 23 ]. While a few studies have examined a role of BKM120 in medulloblastoma, [ 24 26 ] no clinical studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a new generation of pan-PI3K inhibitors include BKM120 (buparlisib) and PX-866 (sonolisib), which have high stability and low side effects ( 28 , 29 ). Some studies have demonstrated that the treatment with BKM120 also inhibits AKT phosphorylation, leading to the inhibition of glioma cell proliferation ( 30 ). In addition, in vivo studies have shown that BKM120 reduces the volumetric increase of the tumor and prolongs survival of nude rats harboring human GB xenografts ( 30 ).…”
Section: Rationale Of Targeted Phosphoinositide 3-kinase/protein Kinamentioning
confidence: 99%
“…Some studies have demonstrated that the treatment with BKM120 also inhibits AKT phosphorylation, leading to the inhibition of glioma cell proliferation ( 30 ). In addition, in vivo studies have shown that BKM120 reduces the volumetric increase of the tumor and prolongs survival of nude rats harboring human GB xenografts ( 30 ).…”
Section: Rationale Of Targeted Phosphoinositide 3-kinase/protein Kinamentioning
confidence: 99%